Demographic profiles and sleep quality among patients on methadone maintenance therapy (MMT) in Malaysia - Zahari, Zalina; Lee, Chee Siong; Musa, Nurfadhlina; Mohd Yasin, Mohd Azhar; Tan, Soo Choon; Mohamad, Nasir; Ismail, Rusli (Faculty of Pharmacy, University of Karachi, 2016)
Poor sleep quality was frequently reported by opioid dependence patients during methadone maintenance therapy (MMT). The study investigated a sample of patients on MMT to investigate the severity and prevalence of sleep problems in MMT patients. We evaluated sleep quality and disturbances of 119 Malay male patients from MMT clinics in Kelantan, Malaysia between March and July 2013 using the Pittsburgh Sleep Quality Index (PSQI)-Malay version. Patients' demographic, clinical data, past drug history and methadone treatment variables were recorded. Patients averaged 37.5 years of age (SD 6.79) and their mean age of first time illicit drug use was 19.3 years (SD 4.48). Their mean age of entering MMT was 34.7 years (SD 6.92) and the mean duration in MMT was 2.8 years (SD 2.13). The mean current daily dosage of methadone was 77.8 mg (SD 39.47) and ranged from 20 to 360 mg. The mean global PSQI score was 5.6 (SD 2.79) and 43.7% patients were identified as 'poor sleepers' (global PSQI scores >5). This study confirms the poor overall sleep quality among patients on MMT. The prevalence and severity of sleep problems in MMT patients should not be underestimated.